The Palolo Worm as a Cornerstone of Pacific Ecological Time-Reckoning - Kelso, Neal; Plunkett, Gregory; Dovo, Presley; Ramík, Dominik; Paul Vusqal, Charlie; Harrison, David; Balick, Michael (Ethnobiology Letters, 2023)
Indigenous knowledge systems that uniquely encode environmental knowledge are vanishing globally in tandem with environmental changes and globalization. In this paper we explore knowledge and uses of the palolo polychaete worms (Palola spp.) in time-reckoning, as documented in the anthropological literature on Polynesia and Melanesia. We then introduce preliminary findings from three contemporary cultures, the Raga-, Vureas-, and Netwar-speaking peoples of Vanuatu. Use of the palolo worm as an element in traditional time-reckoning is well-attested in both historical and contemporary literature, and our original research reinforces the notion that it is still a crucial part of ni-Vanuatu ecological calendars. Within the cultures discussed, the annual appearance of the palolo worm is an important temporal event within very complex systems that incorporate plants, animals, agriculture, celestial bodies, the ocean, and human health for the purposes of organizing human activities. These systems, and the place of the palolo worm within them, must be given proper attention in ongoing efforts towards environmental conservation and the documentation and revitalization of traditional knowledge.